Hypothetical Roles of the Olfactory Tubercle in Odor-Guided Eating Behavior - Murata, Koshi (Frontiers in Neural Circuits, 2020)
Olfaction plays an important role in the evaluation, motivation, and palatability of food. The chemical identity of odorants is coded by a spatial combination of activated glomeruli in the olfactory bulb, which is referred to as the odor map. However, the functional roles of the olfactory cortex, a collective region that receives axonal projections from the olfactory bulb, and higher olfactory centers in odor-guided eating behaviors are yet to be elucidated. The olfactory tubercle (OT) is a component of the ventral striatum and forms a node within the mesolimbic dopaminergic pathway. Recent studies have revealed the anatomical domain structures of the OT and their functions in distinct odor-guided motivated behaviors. Another component of the ventral striatum, the nucleus accumbens, is well known for its involvement in motivation and hedonic responses for foods, which raises the possibility of functional similarities between the OT and nucleus accumbens in eating. This review first summarizes recent findings on the domain- and neuronal subtype-specific roles of the OT in odor-guided motivated behaviors and then proposes a model for the regulation of eating behaviors by the OT.